Bifunctional inhibitors of urokinase and metalloproteinase-9 for cancer treatment - in silico evaluation - Brewer, Shawn P.; Jankun, Jerzy (Translation: The University of Toledo Journal of Medical Sciences, 2018)
Matrix metalloproteinase-9 (MMP-9), and urokinase plasminogen activator (uPA) overexpression or/and increased activity are considered causative elements for cancer invasion and metastasis. These enzymes are degrading the extracellular matrix (ECM) providing space for cancer progression and cancer cell mobility. Process of angiogenesis, in which microvascular endothelial cells form blood vessels, requires local degradation of the underlying basal lamina to invade into the stroma proximal to cancer, and it strongly depends on the activity of MMP-9 and uPA as well. Malignant tumor invasion, cancer metastasis and angiogenesis have been documented as a fundamental factors in the morbidity and mortality among cancer patients, thus their inhibition can be exploit therapeutically. Numerous in vivo and in vitro studies have demonstrated that inhibition of proteolytic activity can reduce caner invasion, tumor size and limit angiogenesis. Consequently human clinical studies were designed inhibiting urokinase or MMPs, but these target specific inhibitors produce mix results. One of the possible explanation could be that cancers are overexpressing more than one enzyme simultaneously – for instance urokinase and MMPs. Thus upregulated net proteolytic activity should be normalized rather than trying to inhibit single proteolytic enzyme. Therefore, starting from specific inhibitors we have created - in silico - several hybrid molecules that could inhibit both uPA and MMP-9. The best hybrid (UI1xAGB) had theoretical affinities of Ki = 1.61-9 mol for MMP-9 and Ki = 1.36-9 mol for uPA. In the future each individual hybrid would need to be successfully synthesized and checked in the in vitro and in vivo analyses.